2006
DOI: 10.1177/0269881106059692
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of N-methyl-D-aspartate receptor function appears to be one of the common actions for antidepressants

Abstract: In order to explore the possible common action mechanisms of three kinds of classical antidepressants, inhibition of drugs on the N-methyl-D-aspartate (NMDA)-Ca(2)-nitric oxide synthase (NOS) signal pathway was observed. With 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay and lactic dehydrogenase (LDH) assay, classical antidepressants, desipramine (1, 10 microM), fluoxetine (0.625-10 microM) or moclobemide (2.5, 10 microM) antagonized NMDA 300 M induced-lesion in PC12 cells. Using fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 11 publications
4
19
0
3
Order By: Relevance
“…This suggests that, besides increasing monoamine levels in the brain by directly inhibiting their reuptake, some antidepressant drugs are also capable of decreasing NO levels (by an unknown mechanism), which could lead to further increases in serotonin levels in the brain. In agreement with that, antidepressants of different pharmacological classes are able to inhibit the function of the NMDA-NOS signaling pathway in vitro (Li et al 2006) and in vivo (Wegener et al 2003), making the inhibition of NO synthesis a central component of the behavioral effects induced by antidepressant drugs. This is further corroborated by the observation that discontinuation of an antidepressant treatment evoked a profound activation of hippocampal NOS activity accompanied by depressive-like behavior in the FST (Harvey et al 2006).…”
Section: Discussionsupporting
confidence: 75%
“…This suggests that, besides increasing monoamine levels in the brain by directly inhibiting their reuptake, some antidepressant drugs are also capable of decreasing NO levels (by an unknown mechanism), which could lead to further increases in serotonin levels in the brain. In agreement with that, antidepressants of different pharmacological classes are able to inhibit the function of the NMDA-NOS signaling pathway in vitro (Li et al 2006) and in vivo (Wegener et al 2003), making the inhibition of NO synthesis a central component of the behavioral effects induced by antidepressant drugs. This is further corroborated by the observation that discontinuation of an antidepressant treatment evoked a profound activation of hippocampal NOS activity accompanied by depressive-like behavior in the FST (Harvey et al 2006).…”
Section: Discussionsupporting
confidence: 75%
“…In this way, it has been demonstrated that inhibition of the NMDA-NO pathway appears to be one of the common actions of antidepressants. Despite remarkable structural diversity, three main kinds of antidepressants (desipramine, fluoxetine and moclobemide) not only antagonized the NMDAinduced lesion in PC12 cells, but also inhibited the function of the NMDA-NO signal pathway (22). These findings are consistent with the hypothesis first proposed by Paul and Skolnick (14) that clinically used antidepressants may share a common ability to block or down-regulate NMDA glutamate receptor function.…”
Section: Introductionsupporting
confidence: 88%
“…The rat adrenal pheochromocytoma (PC12) cell line, possessing typical features of neurons and expressing high level of glucocorticoid receptors (Gao et al 2009), has been widely used in a variety of studies. It has been reported that high concentration of glutamate could also induce neurotoxicity in PC12 cells (Penugonda et al 2005(Penugonda et al , 2006Li et al 2007;Yan et al 2009), while different types of classical antidepressants could protect against cytotoxicity induced by glutamate receptor in PC12 cells (Li et al 2006). These results suggest that cytoprotection against glutamate-induced neurotoxicity may represent one of the action pathways of antidepressants.…”
Section: Introductionmentioning
confidence: 99%